2022
DOI: 10.3389/fmed.2022.1019752
|View full text |Cite
|
Sign up to set email alerts
|

Arterial site selection for measurement of mean arterial pressure in septic shock patients on high-dose norepinephrine

Abstract: BackgroundThe guidelines of the Surviving Sepsis Campaign suggest using invasive blood pressure (IBP) measurement in septic shock patients, without specifying for a preferred arterial site for accuracy in relation to the severity of septic shock. The objective of this study was to determine the mean arterial pressure (MAP) gradient between the femoral and radial artery sites in septic shock patients.MethodThis prospective study was carried out at a 20-bed ICU in a university hospital. Simultaneous MAP measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The basic features of the included studies are summarized in Table 1; and Supplemental Table 2 (http:// links.lww.com/CCX/B343). The earliest article was published in 1987 (29), and the latest article was published in 2022 (6)(7)(8). Twenty-three studies compared the femoral artery with the radial artery, whereas one study compared the femoral artery with the brachial artery.…”
Section: Basic Features Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic features of the included studies are summarized in Table 1; and Supplemental Table 2 (http:// links.lww.com/CCX/B343). The earliest article was published in 1987 (29), and the latest article was published in 2022 (6)(7)(8). Twenty-three studies compared the femoral artery with the radial artery, whereas one study compared the femoral artery with the brachial artery.…”
Section: Basic Features Of Included Studiesmentioning
confidence: 99%
“…Earlier studies have shown variable results regarding the concordance of blood pressure readings from different arterial sites in high-risk surgical and critically ill patients. Some studies found a good correlation between these measurements, while others observed genuine differences in systolic blood pressure (SBP) and mean arterial pressure (MAP) between central and peripheral sites (6–29). This disparity has the potential to influence clinical decision-making and patient outcomes as the accuracy of invasive blood pressure monitoring is crucial in determining the stability of the circulatory system, perfusion to major organs and hence guide the need for interventions.…”
mentioning
confidence: 99%